The effectiveness of positive psychotherapy on the psychological well-being of breast cancer patients - Jamshidifar, Zahra; Shemirani, Shohreh Mortezaei; Ahramian, Afshin; Ahmadi, Armindokht; Lory, Salva Shamsedini; Moradi-Joo, Mohammad (Ciência e Natura, 2015)
Many cancer patients become very anxious and stressed in response to cancer diagnosis. The fear of disease symptoms incidence, the loss of abilities and facing death, creates serious crisis for the patient and threatens one’s well-being. This study aims to determine the effectiveness of positive psychotherapy on the psychological well-being of breast cancer patients. For this purpose, 24 patients with breast cancer in Shohada-e-Tajrish Hospital were selected through available sampling and were tested in terms of psychological well-being questionnaire. The results of analysis of covariance data, showed that positive psychotherapy is effective on the subscales of dominance, relationships and acceptance of psychological well-being in these patients but had no effect on the autonomy, growth, and goal. Therefore, this therapy can be used as an effective approach for the treatment of cancer patients.